2008
DOI: 10.1016/j.mce.2008.06.016
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation F826L in the human androgen receptor in partial androgen insensitivity syndrome; increased NH2-/COOH-terminal domain interaction and TIF2 co-activation

Abstract: A novel mutation F826L in the human androgen receptor in partial androgen insensitivity syndrome; increased NH 2 -/COOH-terminal domain interaction and TIF2 co-activation, Molecular and Cellular Endocrinology (2007), doi:10.1016/j.mce.2008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…7A). However, this was not the case for the Bag-1L (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) peptide, where only the exchange of the penultimate two amino acids XXXRPX to alanine decreased binding (Fig. 7B).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…7A). However, this was not the case for the Bag-1L (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) peptide, where only the exchange of the penultimate two amino acids XXXRPX to alanine decreased binding (Fig. 7B).…”
Section: Resultsmentioning
confidence: 93%
“…Residues in the BF-3 pocket are also targets for prostate cancer and androgen insensitivity syndrome mutations (63)(64)(65)(66)(67). Our finding that the GARRPR motifs of Bag-1L bind to the BF-3 would therefore strongly implicate Bag-1L in the development or progression of androgen insensitivity syndrome and/or prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This gene includes 8 exons, in which exon 1 codes for the transactivation domain, exons 2 and 3 encode the DNA binding domain, and the 3 ′ part of exon 4 including exons 5-8, code for the ligand binding domain [Quigley et al, 1995]. Previous studies have reported the presence of rare mutations in this gene, however, only in very few hypospadias patients [Hiort et al, 1994;Alléra et al, 1995;Sutherland et al, 1996;Nordenskjöld et al, 1999;Wang et al, 2004;Thai et al, 2005;Wong et al, 2008]. In our present study, we screened a much larger cohort and identified one SNP (rs5919436, g.67024320C>G) that was significantly associated with an increased risk of severe hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…The complex is subsequently translocated to the nucleus where it recognizes the canonical androgen response elements and affects the expression of androgen-regulated genes critical for the development of the male sexual phenotype [Mooradian et al, 1987]. Mutations of the AR gene causes the syndrome of partial or complete androgen insensitivity, but mutations in isolated hypospadias patients have been reported in relatively few cases [Hiort et al, 1994;Alléra et al, 1995;Sutherland et al, 1996;Nordenskjöld et al, 1999;Wang et al, 2004;Thai et al, 2005;Wong et al, 2008].…”
mentioning
confidence: 99%
“…The hydrophobic pocket serves as a binding site for coactivators and promotes the LBD-NTD interaction. The coactivator interactions increase transcriptional activity of the AR [He and Wilson, 2002;Werner et al, 2008;Wong et al, 2008].…”
mentioning
confidence: 99%